Kajian Teori Mengenai Strategi Implementasi Data Governance dalam Manajemen Perusahaan - Nurhalita Wulandari; Muhammad Irwan Padli Nasution (CV SWA Anugerah, 2025)
Data Governance is a systematic approach to data management that includes policies, standards, and procedures to ensure the quality, security, and compliance of data in a company. Effective implementation of Data Governance can improve operational efficiency, support data-based decision making, and ensure regulatory compliance. This study aims to analyze the strategy of implementing Data Governance in company management by reviewing the main components, benefits, and challenges faced. The method used is a literature study by referring to the theories and models of Data Governance that have been developed, such as DAMA (Data Management Association) and technology-based approaches. The results of the study indicate that an effective strategy involves setting clear goals, identifying roles and responsibilities, developing data policies, utilizing supporting technology, and ongoing monitoring and evaluation. Despite challenges such as organizational resistance and technological complexity, proper implementation of Data Governance can provide significant benefits in improving the quality and integrity of company data. Keywords: Data Governance, Company Management, Implementation Strategy, Data Quality, Regulatory Compliance